Justice League unlimited. Season one [videorecording (DVD)]. (Warner Bros. Entertainment Inc., 2019)
Too much power, some think. From their Watchtower in space, the Justice League floats above Earth, with countless new members, including Green Arrow, Supergirl, and Black Canary. Their combined powers are awesome. And although these super heroes fight crime, eridicate evil, and save the world over and over again, a conspiracy against them is growing. Led by the government, funded by Lex Luthor, and fueled by a hidden enemy, Cadmus is born.